A comparison of decomposition rates and biological colonization of leaf litter from tropical and temperate origins - Ramos, Sandra M. (2021)
Litter decomposition is an ecosystem process that allows energy and nutrients transfer from dead plant matter into detrital food webs. Several studies revealed that leaf litter decomposition rates differ across biomes, but the reasons for these differences are not yet clear. Here, we test the role of several leaf litter physical and chemical characteristics as predictors of decomposition rates and whether life forms (evergreen vs. deciduous) differ in decomposition rates. Leaves from dominant riparian trees were collected in four ecoregions (temperate deciduous forest, subtropical seasonal semideciduous forest, tropical Cerrado and subtropical dense ombrophylous forest) and their physical and chemical characteristics were measured. We then determined leaf litter decomposition, colonization by aquatic hyphomycetes and macroinvertebrates in a same stream (i.e., under the same environmental conditions), and consumption rates by shredders under laboratory conditions. Deciduous and evergreen tree species did not differ in the measured litter characteristics, but deciduous leaves decompose faster than evergreens. Leaf litter from tree species from the four ecoregions differed in their physical and chemical characteristics. Litter from temperate deciduous species decomposed faster than litter from the other three ecoregions, generally supported higher aquatic hyphomycete species richness and sporulation rates and higher consumption rates by shredders. There were significant negative correlations between litter decomposition and associated biotic variables and litter initial lignin concentration and lignin:N ratio. We conclude that lignin concentration and lignin:N ratio are important predictors of litter decomposition, although other unmeasured parameters such as micronutrients may also play important roles in this key ecosystem process.